(untitled) (Journal of the College of Education for Women, 2019)
Among the findings of the research are:1. This type of ambiguity is old in use and was adopted by the Arab poets as areaction against hyperbole and as a tendency towards compression of expression thatresults in an. amusing suspension through the use of irony. The Andalusian poetstended to employ this form because it involves interaction and interrogation,2. Furthermore, it indicates the poet’s insight, talent and skill and it is, therefore,regarded as a form. Of verse discourse that appeals to the reader, in contrast tohyperbole.3. Its presence in Andalusian poetry is evident n eulogy and descriptive poetry and itheld a place of prominence as a poetic form in achieving these purposes.4. Through its aesthetic, sensual and kinesthetic features in portraying motion lends ita kind of visual synchron icily by which the poet can create a multitude of verbalsketches.